2012
DOI: 10.4236/jectc.2012.24006
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Baffle on Entropy Generation in Separated Convection Flow Adjacent to Inclined Backward-Facing Step

Abstract: Numerical simulations of a two-dimensional laminar forced convection flow adjacent to inclined backward-facing step in a rectangular duct are presented to examine effects of baffle on flow, heat transfer and entropy generation distributions. The main aim of using baffles is to enhance the value of convection coefficient on the bottom wall. But the useful energy can be destroyed due to intrinsic irreversibilities in the flow by the baffle. In the present work, the amount of energy loss is estimated by the compu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…In a recent study about convection flow over BFS, it was revealed that a baffle mounted onto the upper wall increases considerably the magnitude of maximum Nusselt number at the stepped wall [15]. Likewise, the results of the study of the convection laminar flow over inclined backward-facing steps in a duct with a baffle mounted onto the upper wall show that although the baffle enhances the convection coefficient on the bottom wall [16]. A study was analyzed the heat transfer enhancement of 2D laminar and turbulent mixed convective flows adjacent to backward facing step with baffle installation onto the channel wall using different types of nanofluids.…”
Section: Introductionmentioning
confidence: 86%
“…In a recent study about convection flow over BFS, it was revealed that a baffle mounted onto the upper wall increases considerably the magnitude of maximum Nusselt number at the stepped wall [15]. Likewise, the results of the study of the convection laminar flow over inclined backward-facing steps in a duct with a baffle mounted onto the upper wall show that although the baffle enhances the convection coefficient on the bottom wall [16]. A study was analyzed the heat transfer enhancement of 2D laminar and turbulent mixed convective flows adjacent to backward facing step with baffle installation onto the channel wall using different types of nanofluids.…”
Section: Introductionmentioning
confidence: 86%